Cristina Corsi, Božidar Slapšak, Frank Vermeulen (ur.): Good Practice in Archaeological Diagnostics. Non-invasive Survey of Complex Archaeological Sites, 2013 - Štular, Benjamin (Arheološki vestnik, 2013)
/